Polarization-Independent Mode-Evolution-Based Coupler for the Silicon-on-Insulator Platform - Yun Wang; Luhua Xu; Han Yun; Minglei Ma; Amar Kumar; Eslam El-Fiky; Rui Li; Nicolas Abadiacalvo; Lukas Chrostowski; Nicolas A. F. Jaeger; David V. Plant (IEEE Photonics Journal)
We demonstrate a polarization-independent mode-evolution-based coupler for the silicon-on-insulator platform. The measured coupler has negligible insertion loss over a bandwidth of about 100 nm, i.e., from 1500 to 1600 nm. The measured maximum power imbalances for the polarization-independent coupler are 1.2 and 0.2 dB for the fundamental transverse electric (TE $_\text{00}$ ) mode and the fundamental transverse magnetic (TM $_\text{00}$ ) mode, respectively. Our coupler also has a compact design footprint with mode-evolution region not more than ${75}{-μ {\rm m}}$ long.